2021
DOI: 10.1002/hpm.3322
|View full text |Cite
|
Sign up to set email alerts
|

Does tourism increase CO2 emissions and health spending in Mexico? New evidence from nonlinear ARDL approach

Abstract: This study investigates the nexus between tourism, CO 2 emissions and health spending in Mexico. We applied a nonlinear ARDL approach for the empirical analysis for the time period 1996-2018. Mexico receives a large number of tourists each year, tourism improves foreign exchange earnings and contributes positively to the economic growth. However, tourist activities impose a serious environmental cost in terms of CO 2 emissions which increase health spending. The empirical findings suggest that tourism leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Upon examination of part 2 in the literature review, numerous investigations have concurred with similar conclusions, as demonstrated by Aydin [41], Tinoco [54], Gyamerah and Gil-Alana [60], and Chirilus and Costea [59]. Notably, Fan et al [10] contributed to this discourse by illustrating the existence of an asymmetric relationship between variables.…”
Section: Causality Between Variablesmentioning
confidence: 64%
See 1 more Smart Citation
“…Upon examination of part 2 in the literature review, numerous investigations have concurred with similar conclusions, as demonstrated by Aydin [41], Tinoco [54], Gyamerah and Gil-Alana [60], and Chirilus and Costea [59]. Notably, Fan et al [10] contributed to this discourse by illustrating the existence of an asymmetric relationship between variables.…”
Section: Causality Between Variablesmentioning
confidence: 64%
“…The former underlines the impact of some socio-economic factors on carbon dioxide emissions; while the later highlights the causal links between these variables and our interest variable. Almost all of the empirical studies that have addressed this issue are based on an ARDL model, although a few studies have used a non-linear model [10][11][12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result is like Salehi‐Esfahani et al, 2021 who reveal that tourism industry increased health expenditure in Canada. Fan et al, 2021 also confirmed that CO2 emissions from tourism contribute to Mexico's high rate of health spending. The relationship between natural resource depletion and health indicators reveals that a 1% decline in natural capital increases health expenditure by 0.03%–0.12%.…”
Section: Resultsmentioning
confidence: 90%
“…Studies related to the area of tourism have been increasing in recent years in Mexico, with topics as diverse as the effects of COVID-19 [28]; the effects on the informal economy [29]; tourism of the elderly [30]; the link between tourism, pollution and health [31]; and the factors that affect its demand [32]. Unfortunately there are problems and challenges in determining the tourist demand in Mexico [33], since the tourism statistics that are officially disseminated in Mexico do not have the objectivity or veracity that characterizes knowledge, mainly due to a series of errors, omissions, inconsistencies and even method-ological manipulations revealed by the information capture and processing mechanisms.…”
Section: Motivationmentioning
confidence: 99%